PEMETAAN KERENTANAN PESISIR PULAU SIMEULUE DENGAN METODE CVI (COASTAL VULNERABILITY INDEX) - Ruzana Dhiauddin; Wisnu Arya Gemilang; Ulung Jantama Wisha; Guntur Adhi Rahmawan; Gunardi Kusumah (Universitas Lambung Mangkurat, 2017)
The diversity function of coastal areas requires the increasing need for land and infrastructure that will lead to new problems such as changes in coastal morphology, the occurrence of erosion and accretion, which is supported by the population growth caused the increasing of coastal vulnerable towards hazards. This paper aims to explain the parameters affect Simeulue Island’s coastal vulnerability - beach slope, geomorphology, geology, shoreline change, mean tidal range and mean wave height - and its mapping. The data used were the bathymetry, tide, and currents, the topography of coastal morphology, LANDSAT imagery of 2000 and 2015. To determine the coastal vulnerability level, we implemented CVI (Coastal Vulnerability Index) method of 6 parameters. Finally, we found that CVI from these physical parameters ranges between 1.291to 5.00, which were classified into five classes; 1.291 – 1.826 (very low), 1.826 – 2.449 (low), 2.449 – 2.887 (moderate), 2.887 – 3.651(high), and 3.651 – 5.00 (very high).